Performance Evaluation of Nonlinear IM/DD Optical OFDM with New SLM Scheme - Chhavi Sharma (New Approaches in Engineering Research Vol. 15, 2021)
This paper aimed to describe a low complexity SLM technique for PAPR reduction in optical OFDM system. In this research work, FHT based SLM technique with Riemann sequence as phase factor sequence is proposed for PAPR reduction in OOFDM- IM/DD system. As a transmission method for high-capacity long-haul optical transport networks, optical orthogonal frequency-division multiplexing (O-OFDM) systems have gotten a lot of interest. However, it is also very sensitive to nonlinear effects due to high peak to average power ratio (PAPR) problem as conventional OFDM system. This paper proposes Fast Hartley based selective mapping with Riemann Sequence for PAPR reduction in IM/DD Optical OFDM system. Results show that the proposed method performs better in terms of PAPR and bit error rate performance and it is less complex than other conventional methods. The proposed scheme reduces the peak to average power ratio of OFDM signal as well as improves the BER performance of the system compared to the conventional method. The complexity of the proposed method is also less with the use of Riemann sequence and FHT based OOFDM.